ANALISIS PENGGUNAAN MEDIA GAMBAR DIAM MATA PELAJARAN SOSIOLOGI SMA NEGERI 2 SUNGAI AMBAWANG - Akbar, Hariyadi; Rustiyarso, Rustiyarso; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe acquisition of learning outcomes in Sociology education subjects is less satisfying. The acquisition of learning outcomes does not meet the mastery of classical learning. The low acquisition of student learning outcomes in sociology lessons tends to be caused by students not understanding the meaning contained in the subject matter, so that students tend to answer questions by guessing (chancy). In the delivery of absolute sociology subject matter there is a medium of still images because remembering the role of the picture media in delivering sociology lessons students will be more understanding and clear about what is conveyed by the teacher. Based on this reasoning, the writer has encouraged the researcher to examine the use of stationary image media in sociological subjects of class X students of Sungai Ambawang Senior High School 2. In general, the problem in this study is "How is the use of stationary image media in sociology subjects of grade X students of Sungai Ambawang High School 2?". In general, this study aims to describe the use of stationary image media in sociology subjects of grade X students of Sungai Ambawang Senior High School 2..Â Keywords: Analysis of the Use of Silent Image Media in Sociology SubjectsÂ